Revitalisasi Desa Gemas Ceting (Gerakan Masyarakat Sadar Cegah Stunting) di Desa Lumihe Kecamatan Tabongo Kabupaten Gorontalo - Gobel, Hafni Van; Ariani, Gusti Ayu Putri; Apriana, Rista; Rasyid, Puspita Sukmawati; Ali, Samin M (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Lumihe is one of the villages in the working area of the Tabongo Community Health Center, Tangongo District, Gorontalo Regency and is one of the villages that is a priority for preventing and reducing stunting. In 2021, Tabongo Community Health Center states that most children have participated in the Posyandu program and received complete immunization, but public knowledge and awareness about stunting is still weak. Untreated stunting can cause various health problems such as degenerative diseases, diabetes and ARI so that efforts are needed to resolve these problems, one of which is through community empowerment consisting of mothers who have stunted toddlers, Family Health Empowerment (PKK) and health cadres. Through the revitalization of the GEMAS CETING village (Aware Community Movement to Prevent Stunting) in Lumihe, it is hoped that the community can see, recognize and overcome existing problems and have solutions to problems related to stunting.